The Image of Women in The Film "Hati Suhita" Director Archie Hekagery - Sukma Intan Nurima, Alifia; Dwi Rahmayantis, Marista; Waryanti, Endang (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2024)
This research is motivated by observations and experiences regarding the position of women who tend to be underestimated and humiliated in front of men. As a result, many women feel that they are no more capable than men. This is evident from the many things that are done in everyday life with men as the axis. Theoretically, this research uses a feminist approach, while methodologically this research uses a qualitative descriptive method. This type of research is qualitative research that aims to describe conversational data or dialog in the film "Hati Suhita" directed by Arche Hekagery that contains elements of women's image. The data source in this research is the movie "Hati Suhita" directed by Archie Hekagery. The result of this research is that there are four aspects of women's image in the film "Hati Suhita" directed by Arche Hekagery, including the image of women and love, the image of women and suffering, the image of women and responsibility, and the image of women and justice.